The Effect of Glutathione as an Adjuvant Therapy for Skin Whitening and Hyperpigmentation in Type 2 Diabetes - Madiha Soban; Iftikhar Ahmed; Navaid Siddiqui; Faisal Ahmed; Ashar fawad; Tahira Assad Shaikh (ziauddin University, 2024)
Background: Glutathione (GSH) used for skin lightening can also affect Glucose metabolism in diabetics because of its antioxidant properties. This study aimed to determine the effects of systemic glutathione on various parameters in type 2 diabetes. Methods: It was an interventional study (open label trial) conducted at Skin care clinic and Baqai Institute of Diabetes and Endocrinology from August 2019 to January 2020. Total patients included in this study were 46 who met the inclusion criteria along with 20 participants as controls. Oral Glutathione (500 mg B.D) was given to both groups for 18 weeks. Pre and post treatment Plasma Glutathione, fasting blood sugar (FBS), random blood sugar (RBS), and HbA1c levels were evaluated. Taylor hyperpigmentation scale was used to measure skin tone. BMI and Anthropometric measurements were also measured. Paired t-test/dependent t-test and Chi squared test was performed and p < 0.05 was considered statistically significant. Results: Oral Glutathione caused significant reduction in FBS, RBS and HbA1c levels in type 2 diabetics. Mean values of both random and fasting blood sugar significantly decreased in patients group. RBS decreased from 232±10.04 mg/dl to 178±10.37 mg/dl (<0.001*), whereas FBS decreased from 136±10.42mg/dl to 129.24±102.78 mg/dl (<0.002*). HbA1c was significantly decreased in patients group from 7.72 ± 2.04 to 6.66 ± 1.37 (<0.001). Weight, BMI, and systolic blood sugar were also decreased in both groups p=< 0.05, <0.05, 0.005 respectively. Conclusion: Systemic glutathione used for skin tone lightening in diabetics caused significant reduction in FBS, RBS and HBA1c levels. Glutathione can be used as an adjuvant therapy in diabetics. Keywords: Diabetes Mellitus; Glutathione; Skin Pigmentation.